Development of a dual university system health research partnership as a foundation for the Sustainable Development Goals. (March 2018) - Morse, Gene D; Lombardo, Jeffrey C; Forrester, Terrence; Fletcher, Horace; McDonald, Archibald; Talal, Andrew H; Sethi, Sanjay; Tsuji, Brian; Govindaraju, Venu; DeHovitz, Jack; Lindo, John F
Abstract: Background: An innovative dual-system collaboration between the University of the West Indies and the State University of New York was created and implemented by a joint Health Research Faculty Task Force to establish a platform for education and research that would yield an integrated approach to the Sustainable Development Goals (SDGs). Methods: Following the establishment of a joint Center for Leadership and Sustainable Development, a needs assessment was conducted to identify research and education priorities that would benefit from a dual-system linkage structure. Partnerships were facilitated using HUBzero—an open-source software platform with project-specific faculty and staff assigned to each development group. Findings: Programmes in virology research; antimicrobial resistance and stewardship; liver, kidney, and metabolic diseases; and autoimmune diseases, together with the creation of a Clinical Research Center, were identified as highest priorities. Cannabinoid sciences and a joint effort in cancer research, natural products, and nanotechnology to identify indigenous compounds and develop nanomedicine were also key areas. A working group focused on a strategy for workforce planning through science, technology, engineering, and mathematics has also been implemented. Interpretation: This programme uses innovative technology platforms to promote shared project development and is a novel alternative to the traditional model that requires travel and prolonged visits at different training sites. A framework is now established to enable the Joint Health Research Faculty Task Force to begin implementation of high-impact health research initiatives as a foundation for multiple SDGs and to drive regional timelines and milestones. These education and research programmes will be funded through competitive research grants and used to complete data analytics for budget forecasting to achieve the SDGs. Funding: None.